Analysis of Fractures in Patients With Type 2 Diabetes Treated With Empagliflozin in Pooled Data From Placebo-Controlled Trials and a Head-to-Head Study Versus Glimepiride - Kohler, Sven; Kaspers, Stefan; Salsali, Afshin; Zeller, Cordula; Woerle, Hans J. (Diabetes care, 2018)
To assess the effect of empagliflozin on bone fractures and bone mineral density in patients with type 2 diabetes in pooled placebo-controlled trial data and a head-to-head study versus glimepiride. Pooled data were analyzed from patients who were randomized 1:1:1 to empagliflozin 10 mg, empagliflozin 25 mg, or placebo in phase I-III clinical trials. Data were also analyzed from the EMPA-REG H2H-SU trial in which patients received empagliflozin 25 mg or glimepiride as an add-on to metformin for 104 weeks with a 104-week extension. Bone fracture adverse events (AEs) were evaluated through a search of investigator-reported (nonadjudicated) events. In the pooled analysis, bone fracture AEs were reported in 119 of 4,221 (2.8%), 105 of 4,196 (2.5%), and 123 of 4,203 (2.9%) patients in the empagliflozin 10 mg, empagliflozin 25 mg, and placebo groups, respectively (rates of 1.55, 1.36, and 1.69/100 patient-years, respectively). In the EMPA-REG H2H-SU trial, bone fracture AEs were reported in 31 of 765 (4.1%) patients receiving empagliflozin 25 mg and in 33 of 780 (4.2%) patients receiving glimepiride (rates of 1.28 and 1.40/100 patient-years, respectively). Empagliflozin did not increase the risk of bone fracture compared with placebo in a pooled analysis of >12,000 patients or compared with glimepiride in a 4-year head-to-head study.